Assessment of the impact of the industrial enterprise on the environment by determining the integrated (generalized) energy efficiency performance indicator - Gafurov Mirzokhid; Sadullaev Nasullo (E3S Web of Conferences, 2023)
The article summarizes the efficiency indicators. The authors have developed comprehensive efficiency indicators of the enterprise for a complete assessment of the efficiency of energy use. The comprehensive efficiency index of the enterprise is divided into three stages: generation of energy, energy transmission and energy consumption. In this case, the efficiency of using primary energy resources in the enterprise was accepted as a priority criterion. The integrated (generalized) energy efficiency indicator of the industrial enterprise was developed taking into account the participation of renewable energy sources in the energy consumption of the enterprise and the impact of energy consumption on the environment. The most effective way to green production and reduce carbon emissions per unit of product is through energy efficiency testing. Capturing and reducing carbon emissions per product can be achieved through energy efficiency research. It has good energy efficiency in terms of production quality and ease of production methods. The article describes in detail not only the evaluation methodology for evaluating the impact of production on the environment, but also the energy intensive in the production of unit of product and the coefficient of efficiency work in energy production and transmission in generalized indicators.